Adaptation Strategies to Climate Variability and Change and its Limitations to Smallholder Farmers. A Literature Search - Phillipo, Frank; Bushesha, Magreth; Mvena, Zebedayo S. K (Asian Journal of Agriculture and Rural Development, 2015)
In sub-Saharan Africa, knowledge on adaptation strategies to climate variability and change are scattered and fragmented due to lack of standpoints adaptation framework. This paper intends to analyse differences in adaptation strategies across agro-ecological zones, and finding out factors dictating adaptation to climate variability and change to smallholder farmers. The paper is based on documentary review methodology in which journals and books on adaptation were used as the main sources of information. The collected information were analysed by using content analysis. This paper found that smallholder farmers use a variety of practices to adapt to climate variability and change. These practices include: crop management, livestock management, diversification of livelihood strategies and land use management. Availability of extension services, climate change information and membership to social networks were among the factors identified dictating smallholder farmers adaptation to climate variability and change. The paper recommends to the Government of sub-Saharan Africa and development partners to come up with adaptation framework that takes into consideration differences in geographical location. They are needed also to provide enabling conditions to smallholder farmers through strengthening farmers’ supportive services to enhance their adaptive capacities.